Unboxing The Dynamics of Land and Natural Resource Management in Indonesia: Anne Booth, Chris Manning, and Thee KianWie, Land, Livelihood, the Economy and the Environment in Indonesia: Essays in Honour of Joan Hardjono (Jakarta, Yayasan Pustaka Obor, 2012) - Andini Desita Ekaputri (RMPI-BRIN, 2016)
-